The Impact of Rehabilitation on the Aced-Base State of Blood of Patients with COVID-19 in the Intensive Care Unit: a Randomized Trial - Vadim T. Khasanshin; Elena S. Sabiryanova; Vladimir A. Bagin; Dmitrii V. Belskii (Вестник восстановительной медицины)
INTRODUCTION. The need to develop an effective rehabilitation complex for patients with acute viral pneumonia in the intensive care unit (the first stage of rehabilitation).